Impacto da pandemia de COVID-19 em crianças e adolescentes com excesso de peso: influência do confinamento e do fechamento das escolas na obesidade infantil - Maria Gabriela Brunetta Barth; Rosana Bento Radominski; Adriane de Andre Cardoso Demartini (Sociedade Brasileira de Pediatria, 2023)
The COVID-19 pandemic lockdown caused schools closures, increased sedentary time and greater consumption of ultra-processed foods, an environment that might have aggravated the childhood obesity epidemic. AIMS: To verify the impact of school closure on the body mass index (BMI), on lifestyle habits as well as the prevalence of obesity in children and adolescents. METHODS: Cross-sectional observational study of overweight/obesity patients followed at an Endocrinology referral service. A review of the last pre-pandemic visit and the first visit during the pandemic were carried out, and a questionnaire was applied. RESULTS: 50 patients (31 girls) aged 11.5±2.4 years, interval between visits of 379.5±79.5 days. Twenty-nine (58%) reported an increase in the daily number of snacks, 76% reported greater consumption of ultra-processed foods, while 54% reported eating the same amount of food. Greater sedentary time was also reported. Forty-five patients gained weight and there was an increase of 19.6% compared to pre-pandemic weight, a gain of 9.0 kg (-3.6 to 25.5). The median BMI and its z-score variations between visits were +1.9kg/m2 (-2.9 to +7.7) and +0.11 (-0.93 to +1.47), respectively. The change in adjusted BMI to the median for sex and age was +1.65kg/m2 (-3.60 to +6.90). There was an increase in the prevalence of obesity of 6% in the group. CONCLUSION: Defining the longitudinal change in BMI in the pediatric age group is a challenge. This study showed unhealthy weight gain, increased BMI, increased sedentary time and some difficulties faced by children during quarantine.